Associations Among Nursing Work Environment and Health‐Promoting Behaviors of Nurses and Nursing Performance Quality: A Multilevel Modeling Approach. Issue 4 (14th May 2018) - Cho, Hyeonmi; Han, Kihye
Abstract: Purpose: This study aimed to determine the relationships among the unit‐level nursing work environment and individual‐level health‐promoting behaviors of hospital nurses in South Korea and their perceived nursing performance quality. Methods: This study used a cross‐sectional design. Data were collected using self‐reported questionnaires from 432 nurses in 57 units at five hospitals in South Korea. Nursing performance quality, nursing work environment, and health‐promoting behaviors were measured using the Six Dimension Scale of Nursing Performance, Practice Environment Scale of the Nursing Work Index, and Health Promoting Lifestyle Profile‐II, respectively. Results: Nurses working in units with nurse managers who were characterized by better ability and by quality leadership, and who provided more support to nurses exhibited significantly greater health responsibility and physical activity. Nurses working with sufficient staffing and resources reported better stress management. Positive collegial nurse–physician relationships in units were significantly associated with more healthy eating among nurses. Nurses working in units with sufficient staffing and resources, and who had a higher level of spiritual growth and health responsibility, were more likely to perceive their nursing performance quality as being higher. Conclusions: To improve the quality of nursing practice, hospitals should focus on helping nurses maintain healthy lifestyles, as well as improving their working conditions in South Korea. Organizational support for adequate human resources and materials, mutual cooperation among nurses and physicians, and workplace health‐promotion interventions for spiritual growth and health responsibility are needed. Clinical Relevance: Organizational efforts to provide sufficient staffing and resources, boost the development of personal resources among nurses, and promote nurses' responsibility for their own health could be effective strategies for improving nursing performance quality and patient outcomes.